Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
Preparativos para recibir a Martín Travieso y Antonio S. Barceló.
Keywords: Barceló, Antonio R., 1868-1938; Partido Unión de Puerto Rico; Travieso, Martín, 1882-1971